Data on characterization and performance of aspartic acid functionalized graphene oxide-polysulfone mixed matrix membranes - Omnya Abdalla (17100211) (2020)
Structure and microstructure characterization are very important for determining the membrane hydrophilicity, morphology, porosity, and mechanical properties that affect the membrane separation performance and durability. This article analyzes the morphological differences between graphene oxide (GO) and functionalized graphene oxide (f-GO) based on data from SEM imaging. nalysis of the morphology of mixed matrix membrane (MMMs) through SEM, mechanical properties through DMA and hydrophilicity through contact angle data. This dataset will support the original research article “Mixed matrix membranes containing aspartic acid functionalized graphene oxide for enhanced oil-water emulsion separation” (Abdalla, Wahab and Abdala, 2020; doi.org/10.1016/j.jece.2020.104269). The data reported here also include raw data for stress vs strain measurements, mass recorded during permeation test and pure water fluxes at different pressures for all prepared MMMs. Other Information Published in: Data in Brief License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.dib.2020.106197